Effects of spermine and putrescine polyamines on capsaicin accumulation in Capsicum annuum L. cell suspension cultures - Esra KOÇ; Cemil İŞLEK; Belgizar KARAYİĞİT (Acta Agriculturae Slovenica)
This study examined the effects of different concentrations of spermine (Spm) and putrescine (Put) elicitors on capsaicin production at different times in cell suspension culture of peper (Capsicum annuum L‘Kahramanmaraş Hat-187’.), raised from pepper seeds. Callus was obtained from hypocotyl explants of pepper seedlings germinated in vitro conditions, and cell suspensions were prepared from calluses. Spm (0.1, 0.2 and 0.4 mg l-1) and Put (0.1, 0.2 and 0.4 mg l-1) elicitors were applied on cell suspensions, and control groups free from elicitor treatment were created. The amount of capsaicin in cells was found to be higher in the control groups and samples treated with Spm elicitors when compared to filtrates. The highest increase in the capsaicin amount in cells was determined on day 12 of elicitation with 0.2 mg l-1 Spm application. The highest capsaicin amount passing into the filtrate was determined as 0.1 mg l-1 Spm on day 8. The most effective Put concentration and time on capsaicin amount were found as 0.2 mg l-1 Put on day 12 in both cells and filtrates. The highest total capsaicin was also determined in the 0.2 mg l-1 Spm application on day 12with 312.747 ± 8.70 µg  g-1 of culture. Exogenous treatment of Spm and Put elicitors affected capsaicin accumulation.